Linking Mitigation Actions in Developing Countries with Mitigation Support A Conceptual Framework - Kim, Joy Aeree (OECD/IEA Climate Change Expert Group Papers, 2009)
The Bali Action Plan introduced the notion of linking GHG mitigation action in developing countries with support for such action, in a "measurable, reportable and verifiable (MRV)" manner. However, it does not specify the relationship or link that may be made between nationally appropriate mitigation actions (NAMAs) in developing countries and mitigation support. It also remains unclear whether the MRV requirements apply to the link between NAMAs in developing countries and mitigation support, or to one or both of the separate elements. This paper suggests a number of elements for a possible conceptual framework to "link" mitigation actions with mitigation support, including practical considerations for how one might measure, report and verify progress, with a view to understanding the role for such a framework in a post-2012 agreement. The design of a successful and effective linking framework might aim to achieve a number of specific goals. On the action side, a key goal may be to integrate NAMAs in developing countries into national development plans and to address a significant mitigation opportunities. On the support side, important goals are perhaps cost-effectiveness and how to prioritise spending. For a linking framework to successfully address these issues, both actions and support would need to be measurable, reportable and verifiable (MRV). Building on existing systems, a framework for MRV based on both the actual, possible or planned mitigation actions in developing countries as well as on current (public) mitigation support from developed countries could be a good starting point for further development of a linking framework